Full-Mouth Screw-Retained Implant-Supported Rehabilitation with Multiunit Abutments Using Virtual Guided Surgery and Digital Prosthetics Protocol - Igor Ashurko; Artem Trofimov; Svetlana Tarasenko; Sabina Mekhtieva (Case Reports in Dentistry)
Total rehabilitation is one of the most sophisticated kinds of dental implant-supported prosthetics. The usage of multiunit abutment system allows the clinician an accurate and passive fitting of screw-retained full-arch construction. In addition, it retains a condition of soft and bone tissues around prosthetic construction. The aim of this case is to demonstrate a modern approach in planning and realisation of full-mouth screw-retained dental implant prosthetics. A 59-year-old patient had an extraction of all failed teeth on upper and lower jaws with immediate 16 implant placement (8 implants on maxilla and 8 implants on mandible) using surgical template. Multiunit abutments were installed intraoperatively. Temporary constructions were fixed immediately after surgery. After 3 months of dental impressions, plaster models and their scan were prepared to make final screw-retained zirconium dioxide constructions. Reevaluation of functional and aesthetic result of the treatment was made after 12 months.